2011
DOI: 10.1097/tp.0b013e31822bf790
|View full text |Cite
|
Sign up to set email alerts
|

Survival Determinants in Lung Transplant Patients With Chronic Allograft Dysfunction

Abstract: Although most CLAD patients develop an obstructive pulmonary function, 28% develop a restrictive pulmonary function, compatible with the recently defined restrictive allograft syndrome phenotype. Early-onset CLAD, previous development of NRAD, and the development of restrictive allograft syndrome are associated with worse survival after CLAD has been diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 26 publications
4
90
1
1
Order By: Relevance
“…5,6,18,19 We previously reported a significant subset of patients with chronic lung allograft dysfunction who displayed restrictive functional changes, which we designated as restrictive allograft syndrome. 5 Patients with restrictive allograft syndrome were found to demonstrate significantly poorer survival following the onset of chronic lung allograft dysfunction than patients with bronchiolitis obliterans syndrome (median survival: 541 vs 1421 days, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,18,19 We previously reported a significant subset of patients with chronic lung allograft dysfunction who displayed restrictive functional changes, which we designated as restrictive allograft syndrome. 5 Patients with restrictive allograft syndrome were found to demonstrate significantly poorer survival following the onset of chronic lung allograft dysfunction than patients with bronchiolitis obliterans syndrome (median survival: 541 vs 1421 days, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Although bronchiolitis obliterans syndrome, characterized clinically by irreversible obstructive deficits in pulmonary function tests, [1][2][3][4] remains the major cause of late mortality, we recently described a distinct form of chronic lung allograft dysfunction demonstrating restrictive pulmonary function decline, which we designated restrictive allograft syndrome, 5 and which accounts for 25-35% of chronic lung allograft dysfunction. 5,6 Radiologically, a significant proportion of these patients demonstrated an unusual pattern of interstitial fibrosis, often upper lobe-predominant, associated with traction bronchiectasis in computed tomography scans. Although initial review of restrictive allograft syndrome cases confirmed the presence of interstitial fibrosis, 5 the histopathological correlates of restrictive allograft syndrome have yet to be satisfactorily described.…”
mentioning
confidence: 99%
“…On the other hand a new phenotype has been defined based on a restrictive pulmonary physiology. The entity is defined by using a decline in total lung capacity (TLC) of at least 10% (5) or a progressive decrease in FEV 1 and/or FVC with an increasing or stable FEV 1 /FVC ratio (6). This Restrictive Allograft Syndrome (RAS) accounts for approximately 30% of all patients suffering from irreversible CLAD and 20% of all CLAD patients (5,6).…”
Section: Survival Remains Hampered By Chronic Rejection Of Which the mentioning
confidence: 99%
“…The entity is defined by using a decline in total lung capacity (TLC) of at least 10% (5) or a progressive decrease in FEV 1 and/or FVC with an increasing or stable FEV 1 /FVC ratio (6). This Restrictive Allograft Syndrome (RAS) accounts for approximately 30% of all patients suffering from irreversible CLAD and 20% of all CLAD patients (5,6). Clinically, RAS patients have a median survival of 8 months (versus 35 months for BOS patients) (6).…”
Section: Survival Remains Hampered By Chronic Rejection Of Which the mentioning
confidence: 99%
See 1 more Smart Citation